Penggunaan Media Video Pembelajaran terhadap Hasil Belajar Siswa Kelas III SDN 33 Mataram - Handayani, Novia; Witono, A.Hari; Lestari, Sri (Lembaga Yasin AlSys, 2023)
Currently, teachers rarely use media to expand learning material. Teachers only focus on the text so that students find it difficult to understand abstract material. This research aims to analyze the use of learning video media on student learning outcomes. This method uses a quantitative experimental method of the Action Reaction (RA) type. The population in this study used 3rd grade students at SDN 33 Mataram with a sample of 20 students. Data collection techniques use test techniques. The data was analyzed using quantitative descriptive techniques. The results of this research show that there is an increase in learning outcomes through the use of learning video media in class 3 of SDN 33 Mataram. This is evidenced by the increase in student learning outcomes with an average student learning score in the pre-cycle of 65 with 9 students, a percentage of 45%, an increase in the first cycle with an average of 79 with 13 students, a percentage of 65% and in the second cycle the average was 92 with 19 students with a 95% completion percentage.